Kerja Sama Pemanfaatan Barang Milik Daerah Berupa Tanah Dalam Bentuk Perjanjian Bangun Guna Serah - Putri, Elia Cahya; Soetijono, Iwan Rachmad; Kumalasari, Nuzulia (Lentera Hukum, 2015)
Build Operate and Transfer agreement is the utilization of state property in the form of land by another party by establishing a building and facilities, then utilized within a certain period which has been agreed, for after be handed back the land along with the building or facilities after the expiration of the term. This agreement comes as one of the new development patterns in terms of inviting the private sector to participate in national development and becoming a solution to problems in Indonesia in terms of land and funding. The method used in the writing of this essay is the method of writing normative juridical applying the rules of positive law, in the writing of this essay used several approaches are the approach of legislation, conceptual approach, and case approach. There are three principal in land law that have a role in the implementation of the Build Operate and transfer agreement, there are two ways of acquiring land management rights by investors in Build, Operate and Transfer Agreement, there are through a new concession or bankruptcy auction. KEYWORDS: Build Operate and Transfer Agreement.